Cultural-historical didactics and education theory - Hartmut Giest (Instituto Federal Sul-Rio-Grandense (IFSul), 2020)
Cultural-historical didactics is explained as psychologically based didactics and presented in its essential characteristics, starting from its theoretical grounding. This approach and the relations thereby produced in comparison to educational‐theoretical didactics of Wolfgang Klafki are discussed as a contribution most useful to solve current problems of the classroom.